2001
DOI: 10.1002/1521-3935(20011201)202:18<3617::aid-macp3617>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Interpenetrating Networks of Poly(N-isopropyl-acrylamide) with Anionic and Cationic Polymers

Abstract: A series of interpenetrating polymer networks (IPNs) of poly(N‐isopropylacrylamide) (PNIPA) with anionic poly(acrylic acid) (PAA) and cationic poly[[3‐(methacryloylamino)propyl]trimethylammonium chloride] (PMAPTAC) have been synthesized. The swelling behavior of the IPNs is monitored as a function of both pH and temperature. The swelling ratios of IPNs are significantly larger than those reported for pure PNIPA gels. [PNIPA‐PAA] IPNs show a continuous volume phase transition (VPT) at pHs below the pKa of PAA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 15 publications
1
51
0
Order By: Relevance
“…Prior to making contact angle measurements, homopolymer and block copolymer layers were first treated with methanol, which is a good solvent for both PMAA and PNIPAM. [42,48] The PMAA layers produced by photopolymerization were completely wet by water, as expected. After reinitiation in the presence of NIPAM (and subsequent cleaning to remove any nonbonded PNIPAM chains or residual monomer), static water contact angles of 63 AE 38 were measured, which are similar to the value of the static water contact angle of homo-PNIPAM (70 AE 48) and significantly different from that of homo-PMAA (<108).…”
Section: Growth and Reinitiation Of Pmaa Layersmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to making contact angle measurements, homopolymer and block copolymer layers were first treated with methanol, which is a good solvent for both PMAA and PNIPAM. [42,48] The PMAA layers produced by photopolymerization were completely wet by water, as expected. After reinitiation in the presence of NIPAM (and subsequent cleaning to remove any nonbonded PNIPAM chains or residual monomer), static water contact angles of 63 AE 38 were measured, which are similar to the value of the static water contact angle of homo-PNIPAM (70 AE 48) and significantly different from that of homo-PMAA (<108).…”
Section: Growth and Reinitiation Of Pmaa Layersmentioning
confidence: 99%
“…In deionized water it exhibits lower critical solution temperature (LCST) behavior: at $32 8C PNIPAM undergoes a coil-to-globule phase transition induced by expulsion of water from the chain. [42] Though the thermoresponsive behavior of PNIPAM homopolymers or copolymers (random and block) containing NIPAM as one of the comonomers in the form of random coils and hydrogels in aqueous solution has been extensively investigated, [42][43][44] the behavior of surface-grafted homo-PNIPAM brushes to changes in temperature has been studied only in recent years. Surface plasmon resonance measurements by Lopez et al [28] indicate that the phase transition of homo-PNIPAM brushes occurs over a broader temperature range as compared to the coil-globule transition of PNIPAM chains in solution.…”
Section: Introductionmentioning
confidence: 99%
“…For graft polymers [17] and interpenetrating networks, [20] it is reported that PAA and PNIPA interact by forming a hydrogen bond between the carboxylic group of PAA and the amide group of PNIPA. [31,32] In the present study, the transparency of sI-OR1-PAA5 gel decreased dramatically and the gel became completely opaque due to the effective formation of PAA/PNIPA complexes and not at all to the formation of complexes between AA (or PAA) and NIPA.…”
Section: Synthesis Of Si-nc and Si-or Gelsmentioning
confidence: 99%
“…However, all the PNIPA hydrogels with dual sensitivity described above are based on chemically cross-linked networks prepared using organic cross-linkers such as N,N-methylenebisacrylamide (BIS), [13][14][15]18,20] tripropyleneglicol diacrylate, [11] ethyleneglycol dimethylacrylate, [12] or tetraethyleneglycol dimethylacrylate. [16,19] It is reasonable to assume that the sI-PNIPA hydrogels (sI-OR gels), I-PNIPA hydrogels (I-OR gels), and Co-PNIPA hydrogels (Co-OR gels) prepared in those studies were all mechanically fragile, just like conventional chemically cross-linked PNIPA hydrogels (OR gels), although there is little mention of the mechanical properties of the gels in those reports.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation